2008
DOI: 10.1089/acm.2007.0796
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Chiropractic Management and Pain Clinic Management for Chronic Low-Back Pain in a National Health Service Outpatient Clinic

Abstract: This study suggests that chiropractic management administered in an NHS setting may be effective for reducing levels of disability and perceived pain during the period of treatment for a subpopulation of patients with CLBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…The biggest concentration of full economic evaluations (19 in number) pertained to the use of NCCAM's definition of manipulative and body-based practices (eg, chiropractic, osteopathic manipulation, massage, etc) for the treatment of back pain. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] However, even this subgroup is fairly heterogeneous in terms of the therapy (or therapies) tested and/or the type of back pain treated. Eight of these comparisons involved chiropractic care for back pain; one for chronic, 53 one for acute 57 and six for either type.…”
Section: Unit Of Health Outcome Monetary Units (Eg Us$) Natural Unitmentioning
confidence: 99%
“…The biggest concentration of full economic evaluations (19 in number) pertained to the use of NCCAM's definition of manipulative and body-based practices (eg, chiropractic, osteopathic manipulation, massage, etc) for the treatment of back pain. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] However, even this subgroup is fairly heterogeneous in terms of the therapy (or therapies) tested and/or the type of back pain treated. Eight of these comparisons involved chiropractic care for back pain; one for chronic, 53 one for acute 57 and six for either type.…”
Section: Unit Of Health Outcome Monetary Units (Eg Us$) Natural Unitmentioning
confidence: 99%
“…3,49 Although there is evidence that chiropractic treatment can be effective in treating lower back pain in adults, 50,51 there are few data specifically pertaining to pediatric chiropracty despite its popularity for children.…”
Section: Clinical Responsementioning
confidence: 99%
“…Cognitive-behavioral pain treatment programs are usually combined with a functional rehabilitation approach and prove to be a successful treatment for many (Wheeler, 2007). There are few studies on the use of pain clinics in the management of LBP, however Adam-Wilkey et al (2008) controlled trial compared outcomes in perception of pain and disability for a group of patients suffering with chronic LBP when managed in a hospital by either a regional pain clinic or a chiropractor and reported that reduction in mean pain intensity at the end of the study was 1.8 points greater for the chiropractic group than for the pain-clinic group.…”
Section: Pain Clinics In the Management Of Lbpmentioning
confidence: 99%